Hybrid Learning Design to Minimize Academic Stress of Digital Natives’ Generation in Accounting Course - Binti Mucshini; Siswandari Siswandari (Journal of Educational Science and Technology (EST), 2020)
The digital natives generation (DNG) tends to experience relatively high academic stress if the learning design does not pay attention to its characteristics and culture. This study aims to develop a prototype of a hybrid learning model to minimise such stress amongst prospective accounting teachers. This hybrid learning design combines face to face and online learning using the Design-Based Research (DBR) method with stages of problem analysis when learning, and the development of solutions based on principles and theory. Questionnaires, interviews, FGDs and literature studies were used to collect data which were analysed using quantitative and qualitative descriptive analysis. The study found that the DNG experiences relatively high academic stress in the accounting context, so it is necessary to develop a prototype of a flipped classroom-type hybrid learning model by considering its learning style and academic culture and based on the sociocultural revolution theory. This hybrid learning design remains to be tested in further research for its feasibility and effectiveness in minimising DNG academic stress.